ANALYSIS OF FRACTURE GEOMETRY IN FLUID DRAINAGE AFTER HYDRAULIC FRACTURING. CASE OF WINK MS-09 IN MAKELEKESE FIELD, D.R. CONGO - Rachidi Opuluku; Joel Etshekodi Lohadje; Olivier Kimpesa Dyese; Gracias Kingombe Manianga; Jean Iyolo Lungembo; Dirk Akili Bihivu (Romanian Journal of Petroleum & Gas Technology)
In this paper, we analyze stimulation by hydraulic fracturing with the aim of establishing a relationship between fracture geometry and hydrocarbon drainage. Believes fracturing geometry is an effective means of predicting the productive capacity of a hydrocarbon reservoir and the productivity of a well stimulated by hydraulic fracturing is closely linked to the fracturing geometry. Demonstrate the impact of fracturing geometry on the productivity of a hydrocarbon reservoir. Characterize the different parameters of the fracturing geometry while determining the link between these parameters; highlight the difference between the productivity of the reservoir before and after fracturing and monitor the evolution of productivity in relation to this geometry.